STUDENTS’ RESPONSES TOWADS THE USE OF QUIZZES AS AN ASSESMENT FOR ECONOMICAL MATHEMATICS COURSE - Baharuddin (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2025)
The use of quizzes as an evaluation tool has received a variety of attention from students which still requires a lot of revision and innovation in its implementation. The aims of this research to analyze student responses to the use of quizzes as an assesment tool in the Economical Mathematics course, Mathematics Education Study Program, Faculty of Mathematics and Natural Sciences, Makassar State University. This research uses a qualitative approach involving 25 students from the Mathematics Education study program at Makassar State University. Data was collected using instruments in the form of open questionnaire sheets. Next, the research data obtained was analyzed descriptively qualitatively. The research results provide information that the majority of students responded positively to the use of quizzes as an assesment tool, with various benefits including increasing understanding of the material they have studied as well as training material in preparation for the end of semester assesment. However, in its use there are also challenges for students related to the limited time duration for carrying out quizzes. It is hoped that this research will provide insight into the development of more effective assesment methods in the future.